Application of Client-Centered Theory Using Positive Regard (Acceptance) Techniques to Manage Anxiety in Students Who Are Studying While Working - Sholihah, Maidahtus; Pradana, Charis Rizqi; Fatikh, M. Alfin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Students who work while studying often experience anxiety and difficulty in managing time, which hurts their learning outcomes and emotional well-being. This study aims to understand the initial state of the counselee, the process of applying therapy, and the impact of applying Client-Centered Theory with Positive Regard (Acceptance) techniques in managing the anxiety of these students. This research uses a qualitative approach with observation, documentation, and interview methods, and the type of case study research. The results showed positive changes in the counselee after therapy, including improvements in positive affirmations, emotional management, and social interactions. The counselee began to smile more often, take a deep breath, worship more diligently, and show improvement in interacting with family. In conclusion, applying Client-Centered Theory with Positive Regard (Acceptance) techniques effectively manages the anxiety of students who study while working. This therapy helps counselees to accept themselves, think positively, and improve emotional and social well-being. It is hoped that the counselee will continue to remember Allah as a source of strength and understand that everything happens by His will, including the challenges faced.